Understanding strategy assessment in IS management - Benjamin Mueller; Nils Urbach (Information Systems and e-Business Management, 2021)
In our research, we suggest a process theory for explaining the strategy assessment process and its effect in information systems (IS) planning. The proposed theory is derived from an analysis of practitioners and the practices they employ. Based on a multiple-case study design, we look at the IS management teams of three corporate IS departments and how they prepare for strategy development. The analysis of the projects reveals a stable pattern of activities employed by the three teams to assess their departments' strategic positions and existing strategy. Along with this procedural understanding, our research also produces a detailed look at the outcomes of these managerial practices.
Keywords: 650; IS management; IS strategy; Strategy assessment; Process theory; Case study